Determinants of Manufacturing Firm Performance with Firm Size Moderation: Determinan Kinerja Perusahaan Manufaktur dengan Moderasi Ukuran Perusahaan - Rendi Setya Mahendra; Fauwzi Rahardiansyah; Susy Muchtar (Academia Open, 2026)
General Background Company performance represents a central indicator of business sustainability and financial success in dynamic economic environments, particularly within manufacturing industries that play a strategic role in capital markets. Specific Background Prior studies emphasize corporate governance, ownership structure, leverage, tangible assets, and market valuation as key determinants of firm performance, while firm size is frequently associated with variations in these relationships. Knowledge Gap Despite extensive research, empirical evidence remains limited regarding Indonesian manufacturing firms, especially studies that jointly examine governance characteristics, financial structure, tangible assets, and market-to-book value with firm size as a moderating variable. Aims This study aims to comprehensively examine the relationships between board size, ownership structure, leverage, tangible assets, and market-to-book value on firm performance, measured by return on assets and return on equity, while assessing the moderating role of firm size. Results Using panel data from manufacturing companies listed on the Indonesia Stock Exchange, the findings indicate that leverage, ownership structure, and market-to-book value are significantly associated with firm performance, whereas tangible assets show no significant relationship. Firm size moderates selected relationships, with differing outcomes across performance measures and model specifications. Novelty This study integrates multiple internal firm characteristics within a single analytical framework while explicitly positioning firm size as a moderating factor in the Indonesian manufacturing context. Implications The findings provide empirical insights for corporate managers, investors, and regulators in designing governance structures and financial strategies aligned with firm characteristics in emerging manufacturing markets. Highlights • Board structure, leverage, and ownership are associated with financial performance indicators• Firm size produces varying moderating patterns across performance measures• Market valuation metrics relate differently to accounting-based performance Keywords Firm Performance; Manufacturing Companies; Firm Size; Corporate Governance; Market To Book Value